2021
DOI: 10.1080/14760584.2021.1932474
|View full text |Cite
|
Sign up to set email alerts
|

Expert opinion on the way forward for improving maternal influenza vaccination in India

Abstract: Introduction: : Rates of maternal vaccination against influenza are extremely low in India. An expert panel of obstetric-gynecologists and pediatricians met to develop consensus-based recommendations for improving awareness of the benefits of influenza vaccination during pregnancy in India. Areas covered: : The group discussed experiences of influenza infection in pregnancy and infancy before focusing on maternal vaccination practices in India, including the degree of communication between obstetric-gynecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Even during the 2009 H1N1 pandemic, the acceptance of pandemic influenza vaccine was only 26 per cent in Maharashtra despite free vaccination 33 . Poor sensitization of the care providers was identified as a major barrier to influenza vaccination in pregnant women in India 34 , 35 . It has also been shown that engaging clinicians reduce the missed opportunities for vaccination during antenatal period 36 .…”
mentioning
confidence: 99%
“…Even during the 2009 H1N1 pandemic, the acceptance of pandemic influenza vaccine was only 26 per cent in Maharashtra despite free vaccination 33 . Poor sensitization of the care providers was identified as a major barrier to influenza vaccination in pregnant women in India 34 , 35 . It has also been shown that engaging clinicians reduce the missed opportunities for vaccination during antenatal period 36 .…”
mentioning
confidence: 99%